FRAMING ANALYSIS OF BLOKTUBAN.COM MEDIA IN REPORTING THE CAMPAIGN OF CANDIDATE FOR REGENT OF TUBAN - Irawatiningrum, Satya; Rohid, Nibrosu (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
The large number of online media nowadays displays differences in reportingsome news. This difference is influenced by the journalist’s perspective inconfronting some events. The media implicitly also has its own ideology inpresenting news. News is an ideological construction which sometimes containsthe interests of certain parties. In relation to the Pilkada of Tuban Regency,the BlokTuban.com media frames the campaign coverage of the regentcandidates in its appearance that impact to influence the audience to believe forwhat is written there. This study aims to find out the framing analysis ofBlokTuban.com media when reporting the Tuban regent candidate campaignin 2020. The results show that the sources on BlokTuban.com are moredominated by the contestants for the Tuban regent and deputy regentcandidates. The framing by BlokTuban.com is conducted in various ways,namely the diction of news titles, the selection of information sources, and thediction of words used in news articles. BlokTuban.com builds a positive imagein reporting the contestants of the candidates for regent and deputy regent ofTuban.